Desarrollo moral según género en estudiantes de tercer grado de una institución educativa pública - Callao - Romero Hermoza, Rosa María (2012)
The research aimed to establish the level of moral development and whether or not there were differences in gender among third graders in a school in Callao. The substantive research is descriptive and comparative descriptive design. The sample were 55 students aged 8 – 9 years both sexes who were evaluated with a battery of Piagetan test Forcab of cognitive – affective basic structure formation. The results showed that the students do not reach the high level of moral development, likewise, they also showed significant differences in the level of moral development according to gender for some of the dilemmas, being the girl students who reached better results.